International initiatives for the benefit of senior citizens - Wejner, Sabina (Instytut Socjologii Uniwersytet Wrocławski, 2014)
Population projections clearly indicate that issues concerning population ageing are increasing and pose a serious, continuous, demographic problem for individual states as well as Europe and the world. It should be noted that Western European countries have vast experience in the field of the problems in question, due to the fact that issues of population ageing had occurred much earlier there than they did in Poland. A high ratio of people of retirement age contributes to the fact that the expression “Old Continent” takes on a new meaning. In the face of the population ageing process, numerous entities which protect the interests of the elderly play an important role. They focus primarily on protecting the rights and preventing the marginalization of senior citizens in various spheres of social life. Furthermore, local groups promoting the well-being of the elderly operate in most countries. It is worth noting that the older generation can bring many benefits to intergenerational relationships through their knowledge and rich life experience. This manifests itself primarily in civic activity and social roles taken on and performed by senior citizens.
Keywords: population ageing; quality of life; international organizations